CE: Epilepsy Update, Part 2. (June 2015) - Smith, Gigi; Wagner, Janelle L.; Edwards, Jonathan C.
Abstract : Overview: As new research has increased our understanding of epilepsy and the challenges patients with epilepsy face, the role of the nurse as an educator and advocate has grown. This article, the second in a two-part series, addresses the most important aspects of assessing and caring for patients with epilepsy—highlighting the seizure first-aid instructions that all family members of a patient with epilepsy should have; the teaching points to share with parents of young children with epilepsy; and online epilepsy resources for patients, family members, and health care professionals. The authors also discuss current medical, surgical, neurostimulatory, and dietary approaches to epilepsy treatment. Abstract : This second article in a two-part series addresses the most important aspects of assessing and caring for patients with epilepsy, including current medical, surgical, neurostimulatory, and dietary approaches to treatment.